KONTRIBUSI KECEPATAN, PANJANG TUNGKAI DAN KOORDINASI MATA-KAKI TERHADAP KETERAMPILAN MENGGIRING BOLA DALAM PERMAIANAN SEPAK BOLA SISWA SMPN 5 KOTABARU 2018 - Sitti Maifa; Jusran S (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
The purpose of this study was to find out the relationship together speed, leg length and eye-foot coordination to the dribbling skills in the game of soccer at Kotabaru Senior High School 5 students. The sample used in this study amounted to 40. The method used in this study is a quantitative descriptive method that aims to determine whether there is a contribution of speed, leg length and eye-foot coordination of the dribbling skills in playing football with research instruments are: (1) speed test with distance running 30 meter (2) Leg length measurement using a meter in cm (3) Eye-foot coordination test with a 30-second passing test (4) Ball dribbling test calculated using a stopwatch in seconds. The results of this study indicate that: (1) There is a significant contribution between the speed of the ball dribbling skills of Kotabaru 5 Junior High School students with a value of R2 = 0.302 or 30.2%. (2) There is a significant contribution between the length of the legs to the skill of dribbling with a value of R2 = 0.283 or 28.3%. (3) There is a contribution of eye-foot coordination to the skill of dribbling with a value of R2 = 0.281 or 28.1%. (4) There is a significant contribution of speed, leg length and eye-foot coordination to the dribbling skill with a value of R2 = 0.544 or 54.4%. Keywords: Speed, Leg Length, Eye-Foot Coordination, Ball Dribbling.